From “Patchy Endorsements” to Intentional Advocacy: Deconstructing Bias in the Language of Open Access - Lauren B. Collister; Melissa Cantrell (Journal of Librarianship and Scholarly Communication, 2021)
This paper argues that linguistic features common in discourse around Open Access Publishing are socially constructed in ways that lend themselves to implicit bias against the Open Access (OA) movement. These biases materialize through common linguistic practices such as de-centering OA and highlighting the uncertainty of OA Publishing, resulting in “patchy endorsements” of the status quo of Subscription Publishing. Following previous research that demonstrates how educational content on OA can lead to cognitive load and biases that reinforce the status quo in scholarly publishing, we analyze publicly available, online content from our own institutions with an eye towards how these biases manifest specifically in the practice of librarianship. Using examples from this analysis, we suggest strategies and intentional language that can be used by librarians and other OA advocates to counteract bias and shift towards a construction of OA Publishing as the status quo. While many strategies and difficult negotiations are needed to functionally establish OA as the default in scholarly publishing, language choice is a device through which advocates at any level can advance towards an open-centered culture.